Analysis of Presupposition in English Teaching Materials at SMAN 4 Palu - Zulfikri, Zulfikri (Yayasan Pendidikan Bima Berilmu, 2024)
This study aims to analyze the types of presuppositions in English teaching materials at SMAN 4 Palu. The method used in this research is discourse analysis of the English textbooks used in the eleventh grade, focusing on identifying examples of existential, factual, and structural presuppositions. Data were collected through critical discourse analysis techniques and interviews. The results of the analysis show that the teaching material at SMAN 4 Palu contains various types of presuppositions that can influence students' understanding. Existential presuppositions, such as